Pengaruh Pembelajaran Daring Berbasis E-Learning Terhadap Minat Belajar Siswa Man 1 Lombok Timur Selama Pandemi Covid-19 - Alpiana, hairona (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2023)
Online Learning (in the Networks) is a learning method using a network to communicate, to read, and to write performed at the same time, but it is not in the same room using various technologies and multimedia (computers, video, audio, smartphones, etc.). Learning interest is a sense of liking or being interested and happy on something andlearning activities. Students who have a high learning interest will tend to be diligent, tenacious, enthusiasm in learning, never give up, and happy to face challenges. Meanwhile, the students who have a low level of learning interest will begenerallylazy to learn, and tend to avoid assignments. This study aims to determine the effect of online learning on students’ interest of MAN 1 Lombok Timur. The type of study used was causal associative quantitative research. The subjects of this study were students of MAN 1 Lombok Timur consisted of 71 respondents with proportionate stratified random samplingtechnique. The data collection technique used in this study was a questionnaire. While the data analysis techniques used hypothesis testing. The results of the study showed that the online learning variable had a significant effect on the learning interest with a value of t-count> t-table (5.230 > 1.994).